Senegal scaling week: Workshop report - Ewell, Hanna; Atadokpede, Marine; Siagbe, Golli; Diedhiou, Lamine; Ouedraogo, Mathieu (2025)
The AICCRA Senegal Scaling Week workshop, held at the Hotel les Flamboyants in Saly, Senegal 24-26th February 2025, focused on advancing the responsible and inclusive scaling of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) solutions to enhance resilience among smallholder farmers in Senegal. It brought together 33 people (8 of which were women), from various organizations including ministry of agriculture and livestock, Institute for Agricultural Research (ISRA, CERAAS), advisory and extension agency (ANCAR), agency for meteorology (ANACIM), farmers organizations (RESOPP, ADID, APAFIL) and private sector (Jokalante, URAC) and International organisations (AVSF, ILRI, ICRISAT and Alliance). The objective of the workshop was to support the Senegal cluster in operationalizing the scaling-up framework of the AICCRA project by developing effective CIS and CSA packages and corresponding climate solution profiles. In terms of methodological approaches, presentations were used to explain principles, with small groups' work and plenary discussions in a participative atmosphere used. Based on the concepts and principles shared, participants reflected on their visions, the barriers they face and accelerators or enabling factors to overcome them, and established roadmaps for four practices (climate solutions): the iSAT tool, animal feed, improved climate-smart crop varieties, and a community of practice on sustainable livestock management.